Dog Owners' Interaction Styles: Their Components and Associations with Reactions of Pet Dogs to a Social Threat - Cimarelli, Giulia; Turcsán, Borbála; Bánlaki, Zsófia; Range, Friederike; Virányi, Zsófia (Frontiers in Psychology, 2016)
The bond dogs develop with their owner received increased attention in the last years but no study aimed at characterizing the way in which owners interact with their dogs in their daily life and how this might influence dog behavior. In order to examine how dog owners interact with their dogs, we first analyzed the behavior of 220 dog owners in 8 different standardized situations involving the owner-dog dyad. We extracted 3 behavioral factors related to “Owner Warmth”, “Owner Social Support” and “Owner Control”. Further, we investigated whether owner personality, gender and age are associated with these three factors. Results indicated that older owners scored lower in “Owner Warmth” and in “Owner Social Support” and higher in “Owner Control” than younger owners. Furthermore, owners scoring high in “Owner Control” scored lower in the personality trait Openness and owners scoring high in “Owner Social Support” scored lower in the personality trait Conscientiousness. Finally, we also analyzed whether the dogs´ reaction to an unfamiliar woman’s threatening approach was associated with the owners’ interaction styles. Results showed that dogs that searched for proximity of their owners during the threatening situation had owners scoring higher in “Owner Warmth”, as compared to dogs that reacted more autonomously, approaching the unfamiliar experimenter. Analogies between dog-owner interaction styles and human parenting styles are discussed considering the implications of the present findings for human social psychology as well as the practical relevance for dog welfare and human safety.